2012
DOI: 10.1590/s1678-91992012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanic study of Randia aculeata (Rubiaceae) in Jamapa, Veracruz, Mexico, and its anti-snake venom effects on mouse tissue

Abstract: Abstract:In Mexico, medicinal plants are widely used. The use of Randia aculeata by healers against snakebites has never been scientifically tested in relation to possible effects on blood parameters and muscle tissue damage. Interviews were carried out in Jamapa, Veracuz, Mexico, with local residents to collect information about the traditional use of Randia aculeata. In this locality, seven pieces of fruit from the plant are mixed in a liter of alcohol, and then administered orally against snakebites. By usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…Probably this event is largely due to the fact that the powerful enzymatic system that causes necrosis is inhibited by different phytochemicals, which are in the ethanol extract. 6 Other studies have shown an enzymatic inhibition for the in vitro proteolysis by ethanol extract from Renealmia alpinia as proteolytic activity of venoms and is responsible for a fibrinogen decrease in plasma, in our model it can be seen that fibrinogen is not reduced in groups that received venom and later were administered with the ethanol extract, since when proteases are inhibited, fibrinogen will remain, leading to an antihemorrhagic effect. 11 A minor systemic damage due to the plant can be observed because CK and LDH enzymes only raise their activity in those groups that received the venom, these enzymes increase the muscular damage and when both are raised it represents a cardiac damage 12 , in groups where we administered the plant plus the venom, these increase was not present, and this is consistent with a minor damage found in skeletal muscle and heart, in accordance to earlier studies.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Probably this event is largely due to the fact that the powerful enzymatic system that causes necrosis is inhibited by different phytochemicals, which are in the ethanol extract. 6 Other studies have shown an enzymatic inhibition for the in vitro proteolysis by ethanol extract from Renealmia alpinia as proteolytic activity of venoms and is responsible for a fibrinogen decrease in plasma, in our model it can be seen that fibrinogen is not reduced in groups that received venom and later were administered with the ethanol extract, since when proteases are inhibited, fibrinogen will remain, leading to an antihemorrhagic effect. 11 A minor systemic damage due to the plant can be observed because CK and LDH enzymes only raise their activity in those groups that received the venom, these enzymes increase the muscular damage and when both are raised it represents a cardiac damage 12 , in groups where we administered the plant plus the venom, these increase was not present, and this is consistent with a minor damage found in skeletal muscle and heart, in accordance to earlier studies.…”
Section: Discussionsupporting
confidence: 51%
“…The cytoprotective effect on skeletal muscle, myocardium and blood has also been shown. 6 In light of what is mentioned above, it was our interest to assess whether the protective effect on skeletal muscle and heart is due to the modification, by the plant, of the oxidative stress parameters generated by the snake's venom, and if it contributes to a lower degree of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The ethanol extract of R. aculeata fruit is effective against the venoms of the Crotalus simus and Bothrops asper snakes: the extract decreases the tissue damage of skeletal and cardiac muscles and the loss of red blood cells (Gallardo-Casas et al 2012). It is suggested that extract inhibits the proteolytic enzymes involved in the venom hemotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…People of different countries in America (e.g., Mexico, Colombia, Panama, and Brasil) use the leaves, stems, and fruit of several species of Randia in traditional medicine against a wide range of diseases (e.g., renal, respiratory, circulatory, cancer, malaria, snake bites) and symptoms (e.g., inflammation, pain, diarrhea) (Bye et al 1991, Borhidi & Diego-Pérez 2008, Méndez-Valenzuela & Hernández-Martínez 2009, Erbano & Duarte 2011, Gallardo-Casas et al 2012. In Mexico, ethnobotanical uses of Randia are known since 1,777 with records of Tarahumaras Indians that consumed the fruits of Randia echinocarpa Moc.…”
mentioning
confidence: 99%
“…Stems, leaves and fruits of several Randia genus species contain compounds such as 1-nitropyrene, linoleic acid, palmitic acid, sterols, β-sitosterol, β-sitosterol, campesterol, oleanolic acid acetate, oleanolic acid-3-α-L-arabinoside, and mesembryanthemoidigenic acid, among others, which have been shown to confer biological, antioxidant and various pharmacological properties (Cano-Campos et al, 2011;Kandimalla et al, 2016;Lapikanon et al, 1983). The Randia monantha Benth fruit, known as a "crucetillo" because of the cross shape in which the thorns are presented, is used as an antivenom beverage against poisonous animals and to which various pharmacological properties are attributed, since it is used as an anticancer, antidiabetic, antidiarrheal, to relieve stomachache and many other diseases (Gallardo-Casas et al, 2012). Currently, the fruit is used in various liquors, predominantly: brandy, ethanol, and Jerez wine.…”
Section: Introductionmentioning
confidence: 99%